The Establishment of Cognitive Behavioural Therapy in Argentina - Korman, Guido Pablo (2015)
Although Argentina is well known for the popularity of psychoanalysis, in recent years the field of psychotherapy has been expanded to include cognitive behavioural therapy. At present, cognitive behavioural therapy has become much more common in universities and postgraduate educational programmes in Argentina. This work aims to describe the development of cognitive behavioural therapy in Argentina. First, we will depict some general characteristics of psychology in Argentina. Then, we will refer to the first cognitive behavioural therapists in Argentina, highlighting the trajectories of the local main figures, and the events that paved the road for the development of this model in Argentina, such as the visit of Hans Eysenck to Buenos Aires, the impact of Aaron T. Beck's work, and the presence of Vittorio Guidano. Then, we will describe the various institutions that, in the 1990s, established the Argentinian Cognitive Therapies Association. Finally, we will describe the current development of cognitive behavioural therapy in Argentina, and analyse its characteristics and the challenges of local culture.